Analysis Model of a Small Scale Counter-Rotating Dual Rotor Wind Turbine with Double Rotational Generator Armature - Erturk, Ercan; Sivrioglu, Selim; Bolat, Fevzi Cakmak (Int Journal Renewable Energy Research, 2018)
Dual rotor wind turbines have higher efficiency and they can harvest more energy compared to single rotor wind turbines. In this study a counter-rotating dual rotor wind turbine with double rotational generator armature is modelled with mechanical, aerodynamical and electrical components. The considered model includes permanent magnet synchronous generator (PMSG) and a drive train which represent the mechanical characteristics of the generator. In a dual rotor wind turbine the front rotor extracts some portion of energy from the wind therefore downstream of the front rotor the speed of the air is decreased. The air with reduced speed downstream of the front rotor acts as an inflow for the rear rotor. The speed of the residual wind downstream of the front rotor affects the power output of the dual rotor wind turbine. The resulting torque, aerodynamic power and also electrical power of the counter-rotating dual rotor wind turbine are simulated using MATLAB/Simulink software.
Keywords: Dual rotor wind turbine; counter-rotating wind turbine; wind energy; permanent magnet synchronous generator; double rotational armature generator